Pembiasaan Tilawah Al-Qur’an sebagai Strategi Pembelajaran Pendidikan Agama Islam dalam Meningkatkan Konsentrasi Belajar Siswa Madrasah Ibtidaiyah - Mokhamad Choirul Hudha; Septyana Tentiasih (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the effect of Qur’anic recitation habituation on students’ learning concentration at Madrasah Ibtidaiyah. Qur’anic recitation is not merely a religious ritual but also has pedagogical potential in fostering mental readiness, emotional stability, and learning focus. This research employed a quantitative approach with a correlational design. The research subjects were Madrasah Ibtidaiyah students who regularly participated in Qur’anic recitation activities. Data were collected through questionnaires and classroom observations to measure the intensity of recitation and students’ learning concentration, and were analyzed using descriptive and inferential statistics. The findings reveal that Qur’anic recitation habituation has a positive and significant effect on students’ learning concentration. Structured and consistent recitation activities help create a calm psychological atmosphere, enhance cognitive readiness, and improve students’ ability to maintain attention during learning processes. These results indicate that Qur’anic recitation habituation can be positioned as an effective pedagogical strategy to improve learning quality in Madrasah Ibtidaiyah